The Perioperative Role of the Future - Rothrock, Jane (Operating Room Nurses Association of Canada Journal, 1995)
Let me begin by stating that the role of the Registered Nurse First Assistant is not the only perioperative role of the future. It is a vitally exciting potential role of the future, one rich with varied opportunities. There are lots of other things that perioperative nurses could be doing in the future, also very rich and varied in their potential. We call this role changing the transforming and recreating of ourselves, that is 1995 language. It is re-engineer, restructure, redesign and transform.